Mast cell degranulation in periodontal disease from HIV-infected individuals - Giovanna Ribeiro Souto; Alessandro Oliveira de Jesus; Takeshi Kato Segundo; Paôlla Freitas Perdigão; Fernando de Oliveira Costa; Ricardo Alves de Mesquita (Universidade Estadual de Campinas, 2019)
Aim: The objective was to compare the density and degranulation of mast cells on specimens obtained from individuals diagnosed with gingivitis or chronic periodontitis who were either non-HIV-infected or HIV-infected patients treated with highly active antiretroviral therapy (HAART). Methods: Gingival samples were taken from 16 non-HIV-infected individuals and 17 HIV-infected individuals diagnosed with gingivitis and chronic periodontitis. The samples were processed and stained with 0.3 percent o-toluidine blue. Densities (cells/mm²) and percentages of intact and degranulated mast cells were obtained. Results: No statistically significant differences were observed in the mast cell density and the percentage of degranulated mast cells between non-HIV-infected and HIV-infected individuals diagnosed with gingivitis and chronic periodontitis. Mononuclear inflammatory infiltrate was weakly correlated with the percentage of mast cells degranulated for both groups. Conclusions: There are no differences of the density and degranulation of mast cells in gingival tissue between non-HIV-infected and HIV-infected patients undergoing HAART, both groups with diagnosis of gingivitis or chronic periodontitis. This may be a result of the recovery of the immunologic system by HAART treatment.